Socioeconomic heterogeneity in the effect of health shocks on earnings: Evidence from population-wide data on Swedish workers - Petter Lundborg; Martin Nilsson; Johan Vikström (Institute for Labour Market Policy Evaluation (IFAU), 2011)
In this paper, we test for the existence of socioeconomic heterogeneity in the effect of health shocks on labor market outcomes using register data on the total population of Swedish workers. We estimate fixed effect models and use unexpected hospitalizations as a measure of health shocks. Our results suggest large heterogeneity in the effects, where low educated individuals suffer relatively more from a given health shock. This result holds across a wide range of different health shocks and our results suggest that the heterogeneity increases by age. We test several potential explanations to these results. Extensive sensitivity analyses, including a difference-in-differences matching model, show that our estimates are robust to a number of potential threats. We conclude that socioeconomic heterogeneity in the effect of health shocks offers one explanation to why the socioeconomic gradient in health widens during middle ages.
Keywords: I10; I12; 330; Health; Health Shocks; Socioeconomic Status; Life-cycle; Gesundheit; Sozialer Status; Lebensverlauf; Schweden